ANALISIS PENGADAAN MAKANAN BERGIZI DALAM PENANGANAN STUNTING DI DESA SIMANAERE KECAMATAN GUNUNGSITOLI IDANOI - Kartika Zebua, Agnes; Magdalena Batee, Maria; Surya Dinata Mendrofa, Martha; Artatina Buulolo, Nanny Artatina (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2024)
Stunting is a condition of growth failure in children (body and brain growth) due to malnutrition for a long time. So the child is shorter than normal children his age and has delays in thinking. There are still babies and toddlers in Simanere Village who experience quite high levels of stunting. The causes of stunting are due to the economic problems of families who are classified as underprivileged, the lack of provision of healthy food and the lack of implementation of healthy living by families. The Simanaere Village Government is making efforts to prevent stunting by providing nutritious food for babies and toddlers, but it is still not running optimally because the implementation does not run regularly and continuously every month. The aim of this research is to find out the extent of providing nutritious food in handling stunting in Simanaere Village. The method used is a qualitative approach. The research results show that the main problem occurs due to the budget disbursement process not running smoothly to finance the procurement of nutritious food, so the conclusion from this research is that there is a delay in the distribution of nutritious food for babies and toddlers in Simanere Village due to the budget disbursement process from the relevant agencies which takes months. . So it is recommended that Simanaere Village coordinate with the Gunungsitoli City Health Service and related agencies in providing nutritious food assistance for babies and toddlers.